Aberrant post‐translational modifications in endosomal trafficking are potential therapeutic targets to avert therapy resistance in solid cancers: Dysregulation of PTM‐regulated endosomal interactions presents an opportunity to block oncogenic signalling from multiple receptors by targeting common trafficking pathways. (16th December 2021) - Onglao, Winona; Khew‐Goodall, Yeesim; Belle, Leila; Lonic, Ana
Abstract: Drugs targeting a single TK/RTK in the treatment of solid cancers has not had the same success seen in blood cancers. This is, in part, due to acquired resistance in solid cancers arising from a range of mechanisms including the upregulation of compensatory RTK signalling. Rather than attempting to inhibit individual compensatory RTK—requiring knowledge of which RTKs are upregulated in any given tumour—strategies to universally inhibit signalling from multiple RTKs may represent an effective alternative. Endosomal trafficking of RTKs is a common conduit that can regulate signalling from multiple RTKs simultaneously. As such, we posit that targeting endosomal trafficking—in particular, aberrant post‐translational modifications in cancers that contribute to dysregulated endosomal trafficking—could inhibit oncogenic signalling driven by multiple RTKs and pave the way for the development of a novel class of inhibitors that shift the trafficking of RTKs to inhibit tumour growth. Abstract : Signalling from multiple receptor tyrosine kinases can be regulated by endosomal trafficking and that dysregulation of this trafficking network can lead to uncontrolled receptor recycling and signalling. Targeting aberrant post‐translational modifications that lead to dysregulated endosomal trafficking represents a potential therapeutic intervention to combat oncogenic signalling.